Sew Cute Creatures 12 Fun Toys to Stitch and Love - Vos-Bolman, Mariska ([London] Search Press, Wellwood, 2018)
Sew 12 cute and cuddly characters, choose from Pippa Puppy, Sally Seahorse and Patty Piglet to Miranda Mermaid and Peter Pirate
Handcrafts
1
Keywords: amigurumi; syning